2011
DOI: 10.1007/s10549-011-1770-1
|View full text |Cite
|
Sign up to set email alerts
|

Meeting the physical activity guidelines and survival after breast cancer: findings from the after breast cancer pooling project

Abstract: The 2008 Physical Activity (PA) Guidelines recommend engaging in at least 2.5 hours (10 MET-hours/week) of moderate intensity PA per week (defined as 4 METs) to reduce risk of morbidity and mortality. This analysis was conducted to investigate whether this recommendation can be extended to breast cancer survivors. Data from four studies of breast cancer survivors measuring recreational PA from semi-quantitative questionnaires a median of 23 months post-diagnosis (interquartile range 18 to 32 months) were poole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
119
0
12

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(138 citation statements)
references
References 26 publications
7
119
0
12
Order By: Relevance
“…Two analyses showed a substantial inverse dose-response effect between hours per week engaged in physical activity and breast cancer mortality. 26,27 Similar beneficial metabolic effects have been shown for both aerobic and resistance exercise, but optimal results are achieved with a combination of the two.…”
Section: How Does Body Weight Influence the Prognosis For Breast Cancer?mentioning
confidence: 77%
“…Two analyses showed a substantial inverse dose-response effect between hours per week engaged in physical activity and breast cancer mortality. 26,27 Similar beneficial metabolic effects have been shown for both aerobic and resistance exercise, but optimal results are achieved with a combination of the two.…”
Section: How Does Body Weight Influence the Prognosis For Breast Cancer?mentioning
confidence: 77%
“…Além dos tipos de tratamento, outros fatores também são determinantes na prática de AF autorrelatada das mulheres com CM, como a etnia (Mandelblatt et al, 2011;Smith et al, 2009), na qual mulheres negras foram as que menos atingiram as recomendações, comparadas com hispânicas e brancas; a escolaridade, revelando que um maior nível de escolaridade está associado à um maior nível de prática (Bertram et al, 2010;Holick et al, 2008;Hong et al, 2007;Rogers et al, 2011); o status de peso, em que o aumento do IMC associou-se com o menor nível de AF (Beasley et al, 2011;Bertram et al, 2010;Brown et al, 2014;Holick et al, 2008;Hong et al, 2007;Irwin et al, 2004) e; idade, quando as mulheres de maior faixa etária demonstraram menor prática de AF (Beasley et al, 2011;Bertram et al, 2010;Brown et al, 2014;Holick et al, 2008;Hong et al, 2007;Irwin et al, 2004). Nesta última questão relacionada à idade, constatam-se divergências por meio do estudo de Bertram et al (2010), no qual mulheres mais velhas são relatadas como mais ativas no pós-tratamento quando comparadas as mais novas.…”
Section: Discussionunclassified
“…According to the 2008 Physical Activity (PA) Guidelines, it is recommended to engage in at least 2.5 hours per week of moderate-intensity PA (10 metabolic equivalent task (MET)-hours/week, defined as 4 METs) to reduce the risk of cancer related morbidity and mortality. An enhanced epidemiological study from Jeannette and colleagues evaluated 13,000 breast cancer survivors in the After Breast Cancer Pool Project (ABCPP) from multiple cities in the U.S. and from Shanghai, China [94]. After 18-48 months post-diagnosis, they concluded that engaging in at least 10 MET-hours/week of PA was associated with a 27% reduction in all-cause mortality and a 25% reduction in breast cancer mortality.…”
Section: Breast Cancer and Physical Activity (Pa)mentioning
confidence: 99%
“…After 18-48 months post-diagnosis, they concluded that engaging in at least 10 MET-hours/week of PA was associated with a 27% reduction in all-cause mortality and a 25% reduction in breast cancer mortality. Among these women, 1,508 had an initial breast cancer diagnosis between 1996 and 1997 [94], and their ratio of physical activity (RPA) was classified according to their MET. A lower risk of all-cause death was observed for women who were engaged in an average of 9 or more MET-hours/week of PA, from menarche to diagnosis, when compared with women who did not exercise.…”
Section: Breast Cancer and Physical Activity (Pa)mentioning
confidence: 99%